Sleep disorders in children with asthma. Issue 8 (1st March 2021) - Reiter, Joel; Ramagopal, Maya; Gileles‐Hillel, Alex; Forno, Erick
Abstract: Asthma and sleep disorders are both common in childhood, and often co‐exist in the same child. Moreover, studies have shown that in many children the rate of one is influenced by the other. Sleep disorders can be classified into six different groups—insomnia, hypersomnia, parasomnia, movement disorders, circadian disorders, and sleep‐related breathing disorders. Children with asthma often present with complaints of insomnia with poor sleep quality, difficulty falling asleep and sleep disruptions. These complains are often associated with asthma control. They may also complain of daytime sleepiness and have higher rates of parasomnias, such as night terrors and nocturnal enuresis when compared with their healthy peers. Whether movement and circadian disorders are also more prevalent in children with asthma is less clear. Finally, there is a complex bidirectional interaction between sleep‐related breathing disorders and asthma: poor sleep and sleep disorders may worsen asthma, and asthma, particularly when it is poorly controlled, may impair sleep. In the current review we examine the association of each of the sleep disorders with asthma and review the common pathophysiological pathways. We hope to convince the reader that appropriate management of asthma must include inquiries into the patient's sleep, and vice versa.